Ways to Improve Marketing Research at the FOSFOR HOME Enterprise (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the study of demand for products and services, consumer segment analysis, market segmentation and product positioning in the market, as well as product, price, sales and communication policies, research and forecasting of demand satisfaction are discussed. 'attention is given.